2013
DOI: 10.1371/journal.pone.0064415
|View full text |Cite
|
Sign up to set email alerts
|

Aristaless-Related Homeobox Plays a Key Role in Hyperplasia of the Pancreas Islet α–Like Cells in Mice Deficient in Proglucagon-Derived Peptides

Abstract: Defects in glucagon action can cause hyperplasia of islet α-cells, however, the underlying mechanisms remain largely to be elucidated. Mice homozygous for a glucagon-GFP knock-in allele (Gcggfp/gfp) completely lack proglucagon-derived peptides and exhibit hyperplasia of GFP-positive α-like cells. Expression of the transcription factor, aristaless-related homeobox (ARX), is also increased in the Gcggfp/gfp pancreas. Here, we sought to elucidate the role of ARX in the hyperplasia of α-like cells through analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…While Arx null mice die shortly after birth, hypomorphic Arx mutants are viable. Experiments using these hypomorphic Arx mutant and GCGKO mice showed that GFP‐positive α‐like cell hyperplasia in GCGKO mice with hypomorphic Arx was markedly attenuated. Thus, Arx clearly plays important roles in the differentiation and proliferation of α‐cells.…”
Section: Regulation Of the α‐Cell Mass In Normal Development And Arismentioning
confidence: 99%
“…While Arx null mice die shortly after birth, hypomorphic Arx mutants are viable. Experiments using these hypomorphic Arx mutant and GCGKO mice showed that GFP‐positive α‐like cell hyperplasia in GCGKO mice with hypomorphic Arx was markedly attenuated. Thus, Arx clearly plays important roles in the differentiation and proliferation of α‐cells.…”
Section: Regulation Of the α‐Cell Mass In Normal Development And Arismentioning
confidence: 99%
“…At residue 330 of the mouse ARX gene, seven GCG-triplets were inserted to generate GCG7 mutant (Kitamura et al, 2009). Most of them survived for 3-4 months, few last till 5-6 months (Kitamura et al, 2009, Xu et al, 2013. GCG7 mutant mouse was analyzed as ARX expanded model in genetic study, and its ARX mRNA level was significantly down-regulated to approximately 30% of wild-type level in E15.5 pancreata (Wilcox et al, 2013a).…”
Section: Gcg7 Mutant Micementioning
confidence: 99%
“…Recently some studies show that several ARX mutations could lead to apoptosis of a-cells (Wilcox et al, 2013a, Xu et al, 2013 which is originally proposed in the research on hyperplasia of a-cells induced by absolute or relative deficiency of glucagon secretion in vivo (Hayashi et al, 2009). It is found that expression of ARX mRNA is extremely up-regulated in the huge pancreas of mice lacked pro-glucagon gene, and this compensatory hyperemia could be depressed when ARX gene is mutated in vivo, including GCG7 and P335L mutations (Hayashi, 2011, Hayashi et al, 2009, Xu et al, 2013. In this case the reduction of pancreatic a-cell could be due to an increasing a-cell apoptosis, while the b-cell mass remain no change and some b-cell specific transcription factors show no significantly up-regulated.…”
Section: Apoptosismentioning
confidence: 99%